2009
DOI: 10.1108/01425450910991749
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the line: boundaries of workplace humour and fun

Abstract: PurposeThis paper aims to present exploratory, empirical data from an ethnographic study into workplace humour and fun. It explores the notion that workplace humour and fun are influenced by the creation of boundaries that either enable or constrain activities.Design/methodology/approachQualitative data were gathered from four New Zealand companies within different industries. Mixed methods were used and included semi‐structured interviews, participant observation and document collection.FindingsThe findings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 29 publications
3
84
0
1
Order By: Relevance
“…With respect to fun activities, such endeavors should be strategically implemented and carefully designed to ensure congruence with employees' needs and interests to help ensure maximum benefit. Overall, it should be emphasized that fun should be aligned with the culture of the organization at hand (Plester, 2009;Warren and Fineman, 2007 Another opportunity is to examine the impact of fun on turnover and performance in a single study. They present research has demonstrated that fun curbs turnover, yet research is warranted to test whether fun may or may not detract from other important outcomes at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to fun activities, such endeavors should be strategically implemented and carefully designed to ensure congruence with employees' needs and interests to help ensure maximum benefit. Overall, it should be emphasized that fun should be aligned with the culture of the organization at hand (Plester, 2009;Warren and Fineman, 2007 Another opportunity is to examine the impact of fun on turnover and performance in a single study. They present research has demonstrated that fun curbs turnover, yet research is warranted to test whether fun may or may not detract from other important outcomes at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the atmosphere of ebullience and frivolity encouraged in such workplaces are intended to 'loosen up' the formal modes of behaviour and styles of dress we normally associated with employing organizations (Fleming 2005;Fleming and Sturdy 2009). This is certainly the case in Plester's (2009) study of Culture and Organization the various uses of humour in four New Zealand organizations. In one company, a small IT firm known for its informal organizational culture, transgressive humour is actively encouraged by management.…”
Section: Culture and Organizationmentioning
confidence: 91%
“…Indeed, they go on to note that 'the same instance of humour works in both plateaux and with both effects simultaneously' (2012,16). For example, the type of humorous activities that employees engage in at the high-commitment call centre in Fleming's (2005) study -namely partying, flirting and joking around with colleagues -may be either contestive or repressive depending on the specific context in which such activities take place; moreover, the line that separates the former from the latter may be a rather porous boundary, open to contestation and negotiation, rather than a fixed and impermeable barrier (see also Plester 2009;Plester and Orams 2008). It may not, therefore, be possible, in the end, for critical scholars to make a strict division between rebellious and disciplinary forms of humour in an organizational context if the very same joking practice can be mobilized equally for the purposes of worker subversion and management control (Billig 2005, 203).…”
Section: N Butlermentioning
confidence: 99%
“…Humour is able to predict mating success (Greenross and Miller, 2011), and humour and fun are important parts of a successful working climate and strategic business communication (Plester, 2009;Vuorela, 2005). Whether or not humour is effective in advertising also strongly depends on the context, and this study addresses recruitment advertising, which might be risky for several reasons.…”
Section: Theoretical Foundations Related To the Use Of Humour In Recrmentioning
confidence: 99%